Microscale characterization of the viscoelastic properties of hydrogel biomaterials using dual-mode ultrasound elastography. (May 2016) - Hong, Xiaowei; Stegemann, Jan P.; Deng, Cheri X.
Abstract: Characterization of the microscale mechanical properties of biomaterials is a key challenge in the field of mechanobiology. Dual-mode ultrasound elastography (DUE) uses high frequency focused ultrasound to induce compression in a sample, combined with interleaved ultrasound imaging to measure the resulting deformation. This technique can be used to non-invasively perform creep testing on hydrogel biomaterials to characterize their viscoelastic properties. DUE was applied to a range of hydrogel constructs consisting of either hydroxyapatite (HA)-doped agarose, HA-collagen, HA-fibrin, or preosteoblast-seeded collagen constructs. DUE provided spatial and temporal mapping of local and bulk displacements and strains at high resolution. Hydrogel materials exhibited characteristic creep behavior, and the maximum strain and residual strain were both material- and concentration-dependent. Burger's viscoelastic model was used to extract characteristic parameters describing material behavior. Increased protein concentration resulted in greater stiffness and viscosity, but did not affect the viscoelastic time constant of acellular constructs. Collagen constructs exhibited significantly higher modulus and viscosity than fibrin constructs. Cell-seeded collagen constructs became stiffer with altered mechanical behavior as they developed over time. Importantly, DUE also provides insight into the spatial variation of viscoelastic properties at sub-millimeter resolution, allowing interrogation of the interior of constructs. DUE presents a novel technique for non-invasively characterizing hydrogel materials at the microscale, and therefore may have unique utility in the study of mechanobiology and the characterization of hydrogel biomaterials.